282 The efficacy of fibrin sealants in reducing the post-operative morbidity after inguino-femoral lymphadenectomy in melanoma and vulval cancer: back to the drawing board?. (4th December 2020) - Tranoulis, Anastasios; Georgiou, Dimitra; Gupta, Bindiya; Devaja, Omer; Attard-Montalto, Stephen
Abstract : Introduction/Background: The inguino-femoral lymphadenectomy (IFL) and its associated morbidity remains to date a field of contention. Several intra-operative techniques have been advocated to intimidate the IFL-related complications. Despite the improvements in the IFL technique, apprehension towards operative complications still exists. The intra-operative application of collagen-fibrin sealants (CFS) has emerged as a promising intervention to reduce the IFL-related lymphorrhoea. To ascertain the clinical utility of CFS during IFL, we performed a meta-analysis to draw conclusions about their efficacy with the primary objective of reducing the volume and the duration of lymphatic drainage. A secondary objective was to elucidate its effectiveness in reducing other wound complications. Methodology: MEDLINE, Scopus and Cochrane Database were searched for relevant references from inception until August 2020 in line with PRISMA guidelines. Randomized controlled studies (RCTs) and observational studies (OSs) comparing the post-operative morbidity after IFL with or without the use of CFS were included. The modified Jadad score and the methodologic index for non-randomized studies were used to evaluate the quality of the included studies. Dichotomous variables were assessed using odds ratio (OR), whilst continuous variables were assessed using the standartised mean difference (SMD). Confidence intervals were set at 95%. The DerSimonian-Laird random-effects model was used due to the expected inter-study heterogeneity. Statistical analysis was performed using the RevMan software version 5.3. The level of statistical significance was set at p-value < 0.05. Results: Six RCTs and four OSs encompassing 305 and 221 patients respectively were included. The studies were of moderate quality and characterised by significant clinical heterogeneity. The meta-analysis of RCTs demonstrated that the application of CFS did neither decrease the length of drainage [SDM -0.55 (95% CI -1.34 to 0.23), p=0.17] nor the amount of drained output [SMD 0.46 (95% CI -0.29 to 1.20), p=0.23]. No significant difference was found regarding the incidence of lymphocele(s) formation [OR 0.96 (95% CI 0.56 – 1.65), p=0.88] or other wound complications. The safety profile of CFS was favourable. No severe adverse sequelae were reported. Conclusion: Our findings suggest that the use of CFS was not associated with difference in the incidence of IFL-related lymphorrhoea. Their safety profile was favourable. This evidence is constrained by the data available with an inevitable emphasis on short-term outcomes. In view of the lack of clinical equipoise, more high quality RCTs are warranted to draw firmer conclusions. An attempt should be made at standardising outcome measures, which will improve comparability between studies. Disclosures: None.